2008
DOI: 10.1073/pnas.0800616105
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the chloride transporter Slc26a9 causes loss of tubulovesicles in parietal cells and impairs acid secretion in the stomach

Abstract: Slc26a9 is a recently identified anion transporter that is abundantly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 41 publications
5
125
0
Order By: Relevance
“…(5,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Mouse studies have revealed additional roles for these Slc26 proteins in mammalian physiology: deafness, goiter, and acidosis (Slc26a4, pendrin) (42-44), cochlear motor protein (Slc26a5, prestin) (45)(46)(47), proximal tubule NaCl absorption, nephrolithiasis, and intestinal HCO 3 Ϫ secretion (Slc26a6, Pat-1, CFEX) (8, 48 -52), sperm motility (Slc26a8, Tat-1) (53), and gastric acid secretion (Slc26a9) (14). Additionally, several of the Slc26 proteins have reported sensitivity to WNK kinase phosphorylation (11,13), potentially linking them to hypertension (54 -58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Mouse studies have revealed additional roles for these Slc26 proteins in mammalian physiology: deafness, goiter, and acidosis (Slc26a4, pendrin) (42-44), cochlear motor protein (Slc26a5, prestin) (45)(46)(47), proximal tubule NaCl absorption, nephrolithiasis, and intestinal HCO 3 Ϫ secretion (Slc26a6, Pat-1, CFEX) (8, 48 -52), sperm motility (Slc26a8, Tat-1) (53), and gastric acid secretion (Slc26a9) (14). Additionally, several of the Slc26 proteins have reported sensitivity to WNK kinase phosphorylation (11,13), potentially linking them to hypertension (54 -58).…”
Section: Discussionmentioning
confidence: 99%
“…Slc26a9 protein has been localized to epithelia of the stomach and lung (9,10,14), although mRNA is also detectable in brain, heart, kidney, small intestine, thymus, and ovary (10). The R-region of CFTR was previously shown to increase the activity of Slc26a3 and Slc26a6 by interaction with STAS domains (6,15,16).…”
mentioning
confidence: 99%
“…Mutations reported among the 11 human SLC26 genes underlie autosomal recessive congenital chondrodysplasia (4), diarrhea (5), goiter (6), and deafness (6,7). Engineered null mutations in mouse Slc26 genes with human orthologs as yet unassociated with human disease have generated phenotypes of nephrolithiasis (8,9), distal renal tubular acidosis (10), gastric achlorhydria (10,11), and altered regulation of bicarbonate secretion by duodenum (12) and pancreatic duct (13,14). In yeast, plants, and worms, the sulp gene products mediate transport of SO 4 2Ϫ , whereas in mammals the related SLC26 gene products transport a wide range of monovalent anions in addition to divalent SO 4 2Ϫ and oxalate.…”
mentioning
confidence: 99%
“…They possessed abundant intact mitochondria and well‐developed secretory canaliculi (Fig. 2f), and showed no evidence of ultrastructural alterations that suggest either metabolic cell damage or morphological features similar to those described in acid transporter‐deficient parietal cells 14, 15, 16, 17…”
Section: Resultsmentioning
confidence: 87%